Parenting Sense of Competence and Father Involvement in Parenting - Stevanny Putri Nathalia; Rika Vira Zwagery; Emma Yuniarrahmah (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2026)
This study aimed to find out whether there is a role of Parenting Sense of Competence on father involvement in parenting in Banjarbaru City. The research method used was a quantitative correlational survey with a cross-sectional design, using the Parenting Sense of Competence (PSOC) Scale and the Inventory of Father Involvement. The technique used for sampling was nonprobability sampling, specifically purposive sampling, and data collection was conducted offline. The participants in the field data collection consisted of 213 fathers in Banjarbaru City. Based on the results of the hypothesis test using simple linear regression analysis, the alternative hypothesis (Ha) was rejected and the null hypothesis (H0) was accepted, which means that there was no role of Parenting Sense of Competence on father involvement in parenting in Banjarbaru City (p=0.108 0.05). These findings indicated that aspects of Parenting Sense of Competence (PSOC), namely satisfaction and self-efficacy, did not directly predict father involvement in parenting.